Pengaruh Digitalisasi Arsip terhadap Kualitas Layanan Informasi di Kejaksaan Negeri Sijunjung: Studi Kasus Aplikasi SIPEDE (Sistem Informasi Persuratan dan Disposisi Elektronik) - Arwandi, Leonita; Nelisa, Malta (Lembaga Yasin AlSys, 2025)
Digital transformation in archival management is a strategic necessity in the modern era to enhance efficiency and the quality of information services within government institutions. However, the effectiveness of digital system implementation in legal institutions remains underexplored in a comprehensive manner. This study aims to analyze the implementation of archive digitalization through the SIPEDE application (Sistem Informasi Persuratan dan Disposisi Elektronik), evaluate the quality of information services post-implementation, and assess its impact on improving information service delivery at the Sijunjung District Attorney’s Office. The research employed a quantitative associative method using a survey approach, involving 40 employee respondents. Data collection techniques included observation, questionnaire distribution, and literature review. Data were analyzed using Pearson correlation and simple linear regression. The results show that archive digitalization via SIPEDE has a highly significant effect on the quality of information services, with a Pearson correlation value of 0.993 and an R Square of 0.987. The application positively impacted five core dimensions of the E-SERVQUAL model: efficiency, fulfillment, system availability, privacy, and responsiveness. Additionally, elements of the Records Continuum Model (RCM), including record creation, capture, and organization contributed to improved access and workflow. This study concludes that SIPEDE has effectively enhanced both the technical and functional quality of information services within the Sijunjung District Attorney’s Office.